Description chorographique de la Finlande russe : par Pierre de Friccius. - Friccius, Pierre de (A St. Petersbourg : de lʼimprimerie de F. Drechsler, 1807, 1807)
Digital reproduction, The National Library of Finland, Centre for Preservation and Digitisation, Mikkeli
Keywords: geography; Finland